Acquisition de données en continu sur la matière particulaire de la Baie estuarienne de Marennes-Oléron pendant le bloom printaniter planctonique : effet sur le taux de filtration de l'huître Crassostrea gigas - Heral, Maurice; Razet, Daniel; Prou, Jean (Counc. Meet. of the Int. Counc. for the Exploration of the Sea, (The Hague (Netherlands)) (5 Oct 1989), 1989)
The continuous obtention of different signals has been achieved for 9 days at a -fixed station during May 1988. The speed and direction of the currents have been monitoring concurrently with "in situ" turbidity and fluorescence in relation with the meteorological conditions. The concentration in particulate matter and the planktonic fluorescence fluctuated in direct relation with the water depth, the speed of the current and with the origin of the water masses. The oysters submitted to these large fluctuated conditions showed not constant filtration rate. The filtration calculated by turbidimeters (2 1 h-l g-1 dry weight) was three time less than the one achieved with fluorimeters (61 h-l g-1 dry weight). The filtration rate were fluctuated but not in direct relation with the environmental parameters. A general tendancy to an increase of the filtration rate during the neap tide was demonstrated. L'enregistrement en continu de différents signaux a été réalisé pendant 9 jours en mai 1988. La vitesse et la direction du courant ont été acquises en parallèle avec la turbidité et la fluorescence in situ en relation avec les conditions météorologiques. La concentration en matière particulaire et la fluorescence planctonique fluctuent en relation directe avec la hauteur d'eau, la vitesse du courant et avec l'origine des masses d'eau. Les huîtres soumises à ces grandes fluctuations ne présentent pas un taux de filtration constant. La filtration calculée avec les signaux des turbidimètres (2 1 h-l g-1 de poids sec) est 3 fois inférieure à celle obtenue avec les signaux des fluorimètres (6 1h-lg de poids sec). Le taux de filtration est fluctuant mais pas en relation avec les paramètres environnementaux. Une tendance générale à l'augmentation du taux de filtration pendant les cycles de mortes-eaux est mise en évidence